Integration of Tourism Village to Support the Development of Dairy Cattle Farming in Cijeruk District, Bogor Regency, West Java - Yumita; L. Cyrilla E. N. S. D.; I. Komala (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Tajurhalang Village has the potential to be developed into a tourism village through the integration of the agricultural sector, dairy cattle farming as the main commodity, and natural attractions. Therefore, an analysis was conducted to assess the potential for developing a tourism village based on the support of several stakeholders, namely farmers, village government, related agencies, and visitors to realize tourism village in Tajurhalang, Cijeruk District, Bogor Regency. The parameters assessed include political, economic, sociocultural, technological, legal, and environmental factors. Data collection was carried out using the initial survey method and questionnaire preparation as well as interviews and observations. The prepared questionnaire was tested for validity and reliability prior to data collection. The data obtained were tabulated and analyzed using PESTLE and descriptive analysis. The research result show that all stakeholders strongly agree based on the perception category. The PESTLE analysis indicates that the collaboration of policy, community participation, technological utilization, and effective management significantly supports the development of rural tourism and supported by the strategic roles of stakeholders. This presents a substantial opportunity for the livestock and rural tourism sectors to be developed in the future.